2007
DOI: 10.1590/s1516-14392007000200018
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion control of aluminum surfaces by polypyrrole films: influence of electrolyte

Abstract: Polypyrrole (PPy) films were galvanostatically deposited on 99.9 wt. (%) aluminum electrodes from aqueous solutions containing each carboxylic acid: tartaric, oxalic or citric. Scanning Electron Microscopy (SEM) was used to analyze the morphology of the aluminum surfaces coated with the polymeric films. It was observed that the films deposited from tartaric acid medium presented higher homogeneity than those deposited from oxalic and citric acid. Furthermore, the corrosion protection of aluminum surfaces by PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Previous results have shown that the formation of overoxidized films onto aluminum surfaces depend on the electrolyte (A -) nature. 16 In citric acid medium the plateau potential for galvanostic deposition was 1.5 V vs Ag/AgCl resulting in the overoxidized film that was confirmed by the presence of carbonyl in the FTIR spectrum. …”
Section: Electrodeposition Of Polypyrrolementioning
confidence: 88%
See 3 more Smart Citations
“…Previous results have shown that the formation of overoxidized films onto aluminum surfaces depend on the electrolyte (A -) nature. 16 In citric acid medium the plateau potential for galvanostic deposition was 1.5 V vs Ag/AgCl resulting in the overoxidized film that was confirmed by the presence of carbonyl in the FTIR spectrum. …”
Section: Electrodeposition Of Polypyrrolementioning
confidence: 88%
“…In 0.2 mol.L -1 electrolyte, a porous aluminum oxide layer was formed, favoring the PPy film growth. Furthermore, the higher the monomer concentration was, the faster the oxidation reaction of pyrrole at the aluminum/electrolyte solution interface, and the electropolymerization process commenced at lower oxidation potential 15,16 . Higher electrodeposition potential was undesirable since overoxidized PPy films were formed.…”
Section: Electrodeposition Of Polypyrrolementioning
confidence: 99%
See 2 more Smart Citations
“…PPy has been applied in a number of applications, such as batteries, supercapacitors, sensors, microwave shielding and corrosion protection [3][4][5]. In addition, PPy can be used as conducting filler in insulating polymer matrices in preparation of electrically conducting composites.…”
Section: Introductionmentioning
confidence: 99%